Pentingnya Peran Evaluasi dalam Pembelajaran di Sekolah Dasar - Magdalena, Ina; Nurchayati, Aan; Apriliyani, Dewi (MASALIQ, 2023)
This article is a theoretical study of the importance of the learning evaluation process. Evaluation is a process of making decisions about the quality of an object or activity by involving value judgments based on data and information collected, analyzed and interpreted systematically. This research uses a qualitative method with a type of literature study. The data collection technique is by reviewing books, articles and other sources that are related to the topic of discussion, namely learning evaluation. The results of this study found that learning evaluation is very important to do to find out whether or not a learning system is implemented by educators. Because if an educator does not carry out an evaluation, it is the same as that the educator has no progress in designing a learning system. By evaluating educators, they can improve their competence in class management both in choosing learning methods, media, teaching materials, and so on which can motivate students to learn. One of the competencies that must be possessed by a teacher is learning evaluation.